Green Inclusive: Efforts to Create an Inclusive Environment Through Gardening Activities with Children with Special Needs - Aminah, Nur; Fauziah, Fina Rahma; Lathifah, Sri Garcinia; Homdijah, Oom Sitti; Fatin, Jihan (Universitas Pendidikan Indonesia (UPI), 2021)
Activity partners selected in this service activity were selected using a purposive sample system (subjective sample intended based on the researcher's assessment). Based on observations and informal interviews with partners and the community in Kawali Village, Ciamis, Indonesia, the empowerment of children with special needs and the community through gardening activities in the village is very necessary for land use, increasing productivity, and efforts to create an inclusive community environment. The techniques are counseling, webinars, questions and answers, the direct object method of gardening with special needs children, child gardening at home, learning active methods, descriptive interviews, and practices related to gardening activities. The results of the study are: (1) an increase in public knowledge regarding the child with special needs, (2) creating a friendly environment for crew members, (3) publication of activities published in popular media, and (4) design of sustainable targets for further activities. This community service activity has a good impact and a positive value because the series of activities carried out can be a means of improving a friendly environment for children with special needs, and providing useful knowledge to the Kawali, Ciamis, Indonesia.